ACTIVITY OF ZEBRINA PENDULA SCHNIZL. EXTRACT AGAINST STAPHYLOCOCCUS AUREUS, CANDIDA ALBICANS, AND BACILLUS SUBTILIS - Ririn Puspadewi; Mira Andam Dewi; Anggi Gumilar; Luki Yogaswara Yusuf; Estefania Amaris Ivana; Tiara Parmayani; Alpina Rismayati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Zebrina pendula Schnizl., known for its medicinal properties against dysentery, contains chemical compounds like polyphenols, flavonoids, quinones, and terpenoids. Despite its potential, research on Zebrina pendula Schnizl. remains limited. This study aimed to assess the antimicrobial activity of Zebrina pendula Schnizl. extract against Staphylococcus aureus, Candida albicans, and Bacillus subtilis, using the microdilution method. The stages of the study include determination, phytochemical screening of Zebrina pendula Schnizl., standardization, multilevel extraction using n-hexane, ethyl acetate, and 96% ethanol, and antimicrobial activity testing via microdilution method to determine Minimum Inhibitory Concentrations (MIC) and Minimum Bactericidal Concentrations (MBC).